Early experience with robotic rectopexy. Issue 4 (17th June 2013) - Buchs, Nicolas C.; Pugin, François; Ris, Frederic; Volonte, Francesco; Morel, Philippe; Roche, Bruno
Abstract Background The introduction of robotics in colorectal surgery has been gaining increasing acceptance. However, experience remains still limited for pelvic floor disorders. We report herein our first cases of fully robotic rectopexy and promontofixation for rectal prolapse. Methods From October 2011 to June 2012, five female patients underwent a robotic rectopexy at our institution. The patients were selected according to their primary pathology and their medical history for this preliminary experience. Four of them presented a rectal prolapse associated or not with a vaginal prolapse and the last patient presented a recurrent rectal prolapse 5 years after a laparoscopic repair. The study was approved by our local ethics committee. The robot da Vinci Si (Intuitive Surgical Inc, Sunnyvale, CA) was used with a 4‐port setting in all cases. Results The mean operative time was 170 minutes (range: 120–270). There was no conversion. The blood loss was minimal. One patient presented a retrorectal hematoma, treated conservatively with success. There was no other complication. The mean hospital stay was 3.6 days (range: 2–7). At 2 months, there was neither recurrence nor readmission. In comparison with the laparoscopic approach, there were no statistically significant differences. Conclusions Robotic rectopexy and promontofixation are feasible and safe. The outcomes are encouraging, but functional results and long‐term outcomes are required to evaluate the exact role of robotics for rectal prolapse. Copyright © 2013 John Wiley & Sons, Ltd.